2022
DOI: 10.1002/adem.202200368
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Electrothermal Film Based on Laser‐Induced Graphene

Abstract: The flexible heaters have attracted growing interest due to their wide applications including biosensors, [1,2] gas sensors, [3] defoggers, [4] and microfluidics. [5] Generally, these electrothermal film heaters contain electrically conductive layers that operate under the principle of Joule heating. An excellent electrothermal heater requires not only fast response time, stable working temperature, and uniform temperature distribution but also flexibility, arbitrary shape, biocompatibility, and cost-effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…This implies that different chains could be featured with different microscopic crystallinities/aggregations and different local electronic properties. [ 15,23–27 ] Phase separation between the different sub‐components of polymers, which also refers to microscopically chemical purification, increases the complication of the phase separation in conjugated‐polymer/insulator blends, but provides a potential method to improve the device performance and develop new devices. Effective methods are needed to induce appropriate phase separations to optimize the device construction and charge transport.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that different chains could be featured with different microscopic crystallinities/aggregations and different local electronic properties. [ 15,23–27 ] Phase separation between the different sub‐components of polymers, which also refers to microscopically chemical purification, increases the complication of the phase separation in conjugated‐polymer/insulator blends, but provides a potential method to improve the device performance and develop new devices. Effective methods are needed to induce appropriate phase separations to optimize the device construction and charge transport.…”
Section: Introductionmentioning
confidence: 99%
“…This makes it susceptible to detachment compared to the LIG adjacent to the substrate, leading to easy lamination or the transfer of LIG patterns , to other substrates. To address this adhesion issue, the common practice is to passivate LIG electrodes with a polymer layer. While conducting a peeling adhesion test using acrylic adhesive tape, it was observed that our in situ LIG contacts also displayed weak adhesion to the substrate, resulting in a degradation of device performance. However, passivation applied to the LIG contact significantly improved the adhesion, ensuring consistent device performance throughout the test (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…Diketopyrrolopyrrole (DPP) and isoindigo (IID) units are well‐known building blocks for high‐mobility CPs, owing to their planar and electron‐deficient nature. [ 28–34 ] With DPP and IID derivatives as C─Br monomers and 4FBT and 4FTVT as C─H monomers, high‐mobility CPs with superior OTFT performance have been synthesized via DArP. [ 19,20,22,24,25 ] Apart from oligothiophenes such as thiophene, BT, TVT, and so on, diverse thiophene‐substituted aryls are also important building blocks of high‐mobility CPs.…”
Section: Introductionmentioning
confidence: 99%